Classification of mythological and archetypal images in Kazakh art of painting - Khalima Kh. Truspekova, Balnur R. Karabalaeyva, Yerzhan K. Ryssymbetov, (Opción, 1970)
The article discusses one of the most significant changes in the fine arts during the period of independence - the basics of symbolism, symbolic painting, mythical and archetypal images via comparative qualitative research methods. As a result, the mythologization, which began with the compositions of B. Bapishev, became relevant in the first years of independence and was aimed at re-creating a myth on the basis of ancient beliefs and concepts. In conclusion, the main proposed basis of modern painting is to excite the viewer with personal thoughts and provide food for thought.